Group effects of a non‐native plant invasion on rodent abundance - Bryan M. Kluever; Trinity N. Smith; Eric M. Gese (Ecosphere, 2019)
Abstract Cheatgrass (Bromus tectorum) is the most prolific invading plant in western North America. Investigations determining the impact of this invasion on population state variables and community dynamics of rodents have largely occurred at the community or species level, creating a knowledge gap as to whether rodents affiliated by a shared taxonomy or other grouping are differentially affected by cheatgrass invasion. We examined rodent abundance along a gradient of cheatgrass cover using various groupings of two nocturnal rodent taxa comprising the majority of the rodent community in the Great Basin Desert. In the summers of 2010–2013, rodents were sampled and vegetation was measured on the U.S. Army Dugway Proving Ground in the Great Basin Desert of Utah, USA. We separately examined estimates of rodent abundance for all combined species within the Cricetidae and Heteromyidae families, the most numerically dominant species, and uncommon species pooled in relation to cheatgrass invasion severity. We detected an expected negative linear relationship between invasion severity and abundance for all cricetid groupings, including the most numerically dominant species, the deer mouse (Peromyscus maniculatus). Unexpectedly, heteromyid abundance exhibited an initial positive relationship, reached a threshold, and then exhibited a negative relationship, a phenomenon driven by Ord's kangaroo rats (Dipodomys ordii), the most numerically dominant species. We speculate this non‐linear finding was caused by a combination of trophic and non‐trophic pathways. Our findings provide new insight as to the potential for differential effects of cheatgrass on rodents in arid portions of the western United States. We suggest that future investigations on cheatgrass, and plant invader effects in general, consider parsing animal communities of interest by various taxonomic and/or ecological groupings rather than focusing exclusively on individual species or entire communities.